Level up in tourism education: Unveiling knowledge through the use of quiztour and turismo em forca games - Silva, Allisson Mateus Marques Cavalcanti; Costa, Tali Veloso de Morais; De Guimarães, Julio Cesar Ferro; Borba, Carla Santos (Journal of Sustainable Competitive Intelligence, 2024)
Purpose: The study aims to investigate the effectiveness of gamification in tourism education, addressing how game elements can enhance student engagement and learning. Methodology/approach: Qualitative research with quantitative data. A pilot study was conducted with a master's class in Tourism, utilizing two pedagogical games: "QuizTour" and "Turismo em Forca." Data collection was performed through a survey administered after the game sessions, allowing for a quantitative analysis of responses. Originality/Relevance: This study advances science in the education field by demonstrating the effectiveness of gamification and its practical implications. Key findings: The results indicated that gamification promoted a more dynamic and collaborative learning experience, facilitating the understanding of complex concepts. However, challenges such as the need for well-planned design and lack of technological resources were identified. Theoretical/methodological contributions: Contributions include improvements in pedagogical practice and insights for implementing gamification in educational contexts, as well as strengthening the theoretical foundation on the topic.